Microcomputers and electronic instrumentation : making the right connections. - Malmstadt, Howard V. (American Chemical Society, 1994)
"The authors believe that the effectiveness of future generations of scientists depends in part on their ability to use intelligently, diagnose, and modify their microcomputer-based and electronic instrumentation. Using a "top-down" approach, the authors present electronic concepts, principles, and technology that are impacting our daily lives. They start at the top, by providing a broad perspective of electronic instrumentation, and work down to functional modules, devices, and detailed operations. This top-down approach enables all of the pieces to fit together so that a working knowledge is developed as one proceeds through the chapters. Written specifically for chemists, physicists, engineers, biologists, medical researchers, students, and other technical personnel who can benefit from "making the right connections" to modern instrumentation, this book will empower you to gain better control and make better use of your microcomputers and laboratory instruments." (Copied from the paste).